Fear of China: Economic and Political Challenge in the 21st Century:: A Pacific Society, Weapons, Roots and Trends (Asian Journal of Social Science Studies, 2017)
While the world has been distracted since the American war in Vietnam and the Soviet and western adventures in Afghanistan, as well as a rising tide of rebellion directed against symbols of the west by Islamic fundamentalists, a curious contest has appeared on two fronts: Russia and China. At the same time the west is distracted by populist movements whose theme is focused on immigrants from former colonial nations or non-whites in a context, as in America, where aboriginal peoples have been slaughtered and marginalized. The specific nature of this conflict is economic in general form, yet political in rhetoric, especially from western sources. From the Ukraine to the Pacific a kind of “Phoney War” has crept along in starts and stops with overtures of friendship interrupted with threats of violence and minor acts of aggression. Investigation of some of the underlying factors in the East illuminate potential trends for the future. At the same time a new revitalization movement is reshaping the Anglo-American west, one that challenges the role of China in trade and policy.